Cultivating the worshipful self in an algorithmic age: Reflections on an Asadian conclusion - Rafudeen, Auwais (HTS teologiese studies, 2022)
In a recent book, Secular Translations: Nation State, Modern State and Calculative Reason, Talal Asad is concerned with how the language of calculation and abstraction, inaugurated by modernity and accelerated by our current algorithmic reality, erodes the language of cultivated embodiment typical of religious worldviews and the virtues that such embodiment seeks to develop. These languages are predicated upon and cultivate different types of selves that are fundamentally at variance with each other. It is not that that one cannot cultivate the worshipful, virtuous self in our algorithmic reality, but Asad’s pessimistic conclusion is that the conditions for such cultivation are being made increasingly difficult as we seemingly hasten towards a posthuman future. Asad here echoes thinkers such as Leon Kass and Michael Sandel who have also expressed disquiet about the loss of cultivated embodiment in such a future, but in an important meta sense, he goes beyond them by interrogating the underlying language we use to frame our discussions in this area. The purpose of this article is to bring an awareness to this Asadian argument, which, I believe, should at the very least give us some pause for thought as technology plunges us into new and unknowing horizons. Contribution: Despite the many laudable accomplishments of modernity in the techno-scientific sphere, vital questions remain about its ability to bring about overall human flourishing. Among others, the thought of Talal Asad provides a way to think about why the promised potential of modernity in this regard has not been realised and, concomitantly, why traditional, embodied teachings of religion continue to be critical in thinking about the future.